Agronomic performance of tropical × tropical and tropical × temperate single-cross maize hybrids in Ibadan, Nigeria (2018)
The productivity of tropical maize could be improved by the introgression of beneficial alleles from temperate germplasm. Ten tropical × temperate and two temperate × temperate single cross hybrids were developed and evaluated for their performance alongside four tropical × tropical hybrids. The tropical × temperate hybrids were developed by crossing the temperate inbred lines B73 and Mo17 as males to the tropical inbred lines 4001, 4008, 9613, 9432 and KU1409. The experimental design was randomized complete block with three replicates. Data were collected on seedling emergence, flowering traits, grain yield and yield components and subjected to analysis of variance. Significant genotypic differences were observed among the hybrids for all measured traits. The tropical × tropical crosses had significantly higher grain yield, ear width, kernel weight and kernel depth than the crosses involving the tropical × temperate inbred lines. However, the tropical × tropical hybrids had lower emergence percentage, but higher emergence index and emergence rate index than the tropical × temperate hybrids. Grain yield ranged from 3.38 (Mo17 × B73) to 6.02 t/ha (4001 × 4008) and was in the order temperate × temperate < tropical × temperate < tropical × tropical hybrids. On average, tropical × B73 hybrids had higher grain yields than tropical × Mo17 hybrids. Four of the tropical × temperate hybrids (4001 × B73, 4008 × B73, KU1409 × B73 and 9432 × Mo17) had grain yields equal to or above the overall average. These hybrids have considerable potential and could be exploited to improve and broaden the grain yield of tropical maize.